Temperature‐dependent development of Aproceros leucopoda (Hymenoptera: Argidae), an invasive pest of elms in Europe. (9th March 2018) - Papp, V.; Ladányi, M.; Vétek, G.
Abstract: The temperature‐dependent development of Aproceros leucopoda Takeuchi, 1939 (Hymenoptera: Argidae), an invasive pest of elms in Europe, was studied in the laboratory on Siberian elm ( Ulmus pumila ) at six constant temperatures (10.9, 15.0, 19.5, 23.0, 24.3 and 27.0°C) and at a photoperiod of 16L:8D. The larvae of the species developed through 4–7 instars, and it was the 6th instar individuals of which continued their development at the highest rate. The developmental threshold ( T min ) and the thermal constant ( K ) were determined by the linear model and Lactin‐2 model for egg, larval, prepupal and pupal stages and one whole generation. The estimated values of T min and K by the two models for one generation were 7.3 and 7.1°C, and 426.5 and 432.7 degree‐days, respectively. Based on the survival and fecundity rates, the optimal temperature range for the species may be expected to be between 15.0 and 19.5°C. Allowing for the period of diapause, it was estimated that A. leucopoda might potentially develop through up to four or five generations per year in Hungary. These results may contribute to the better understanding of the biology of an invasive alien species in Europe.